Development of a mobile application for realtime location management and assistance for visually impaired individuals - Piedra Vargas, Kenneth (2025)
The project focuses on the development of a mobile application, “PathWhisper,” designed for visually impaired individuals. Its main purpose is to provide real-time information about their location and surroundings through clear and precise voice prompts from a virtual assistant powered by artificial intelligence and machine learning. This application goes further, becoming a travel companion that describes various physical environments, allowing users to build a partial understanding of their journey.